Value Determination of Supply Chain Initiatives A Quantification Approach Based on Fuzzy Logic and System Dynamics - Wessely, Philip; SpringerLink (Wiesbaden Gabler, 2011)
The implementation of supply chain initiatives (SCI) often requires specific investments in technology, material, organization and staff. However, the assessment of the economic viability of such inter-organizational activities is not a trivial issue. Philip Wessely supports managerial decision-making in the forefront of a potential implementation by introducing a quantification approach for the value contribution of SCIs. The resulting approach combines different innovative modeling techniques and considers the individual integration of companies in inter-organizational networks. As a result, it has a broad field of application.
Conceptual Framework for the Consideration of Individual Applications of SCIs; A Fuzzy Model for the Quantification of an SCI's Revenue Contribution; A System Dynamics Simulation for the Determination of Changes in Costs and Capital Commitment
Electronic reproduction.
Keywords: Business logistics; Electronic books